The STRATAA study protocol: a programme to assess the burden of enteric fever in Bangladesh, Malawi and Nepal using prospective population census, passive surveillance, serological studies and healthcare utilisation surveys. Issue 6 (2nd July 2017) - Darton, Thomas C; Meiring, James E; Tonks, Susan; Khan, Md Arifuzzaman; Khanam, Farhana; Shakya, Mila; Thindwa, Deus; Baker, Stephen; Basnyat, Buddha; Clemens, John D; Dougan, Gordon; Dolecek, Christiane; et al.
Abstract : Introduction: Invasive infections caused by Salmonella enterica serovar Typhi and Paratyphi A are estimated to account for 12–27 million febrile illness episodes worldwide annually. Determining the true burden of typhoidal Salmonellae infections is hindered by lack of population-based studies and adequate laboratory diagnostics. The Strategic Typhoid alliance across Africa and Asia study takes a systematic approach to measuring the age-stratified burden of clinical and subclinical disease caused by typhoidal Salmonellae infections at three high-incidence urban sites in Africa and Asia. We aim to explore the natural history of Salmonella transmission in endemic settings, addressing key uncertainties relating to the epidemiology of enteric fever identified through mathematical models, and enabling optimisation of vaccine strategies. Methods/design: Using census-defined denominator populations of ≥100 000 individuals at sites in Malawi, Bangladesh and Nepal, the primary outcome is to characterise the burden of enteric fever in these populations over a 24-month period. During passive surveillance, clinical and household data, and laboratory samples will be collected from febrile individuals. In parallel, healthcare utilisation and water, sanitation and hygiene surveys will be performed to characterise healthcare-seeking behaviour and assess potential routes of transmission. The rates of both undiagnosed and subclinical exposure to typhoidal Salmonellae (seroincidence), identification of chronic carriage and population seroprevalence of typhoid infection will be assessed through age-stratified serosurveys performed at each site. Secondary attack rates will be estimated among household contacts of acute enteric fever cases and possible chronic carriers. Ethics and dissemination: This protocol has been ethically approved by the Oxford Tropical Research Ethics Committee, the icddr, b Institutional Review Board, the Malawian National Health Sciences Research Committee and College of Medicine Research Ethics Committee and Nepal Health Research Council. The study is being conducted in accordance with the principles of the Declaration of Helsinki and Good Clinical Practice. Informed consent was obtained before study enrolment. Results will be submitted to international peer-reviewed journals and presented at international conferences. Trial registration number: ISRCTN 12131979. Ethics references: Oxford (Oxford Tropical Research Ethics Committee 39-15). Bangladesh (icddr, b Institutional Review Board PR-15119). Malawi (National Health Sciences Research Committee 15/5/1599). Nepal (Nepal Health Research Council 306/2015).